THE FACTORS OF CONSUMER BEHAVIOR IN DECIDING TO BUY SANMOL SYRUP DRUG AT SIMPANG EMPAT PHARMACY PALEMBANG - Bambang Dwiatmanto; Fathorrahman Fathorrahman; Theresia Pradiani (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
The purpose of this study was to determine the factors that influence the decision to buy Sanmol Syrup at the Simpang Empat Palembang Pharmacy.The sample size taken was 59 samples. The sampling technique used was an accidental sample, namely, where the respondents who were taken were samples that happened to meet the researcher when buying Sanmol Syrup. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 27 statement items. The analysis technique used simple linear regression analysis. The results show there is a cultural influence on purchasing decisions, there is a social influence on purchasing decisions, there is a psychological influence on purchasing decisions